The Effect of Cement Thickness on Shear Bond Strength of Zirconia with Three Different Self-Adhesive Resin Cements - Ieamsuwantada, Thofun; Yamockul, Suparaksa; Thamrongananskul, Niyom; Surintanasarn, Atikom; Klaisiri, Awiruth (European Journal of Dentistry, 2025)
This study aimed to evaluate the influence of resin cement thickness on the shear bond strength (SBS) of zirconia bonded with three different self-adhesive resin cements (SACs).One hundred and twenty zirconia specimens were prepared. Zirconia disks were milled into a cuboidal shape of size 8 × 8 × 6 mm3 using a milling machine, sintered according to the manufacturer's instruction, polished with sandpaper, airborne particle abraded with 50 μm aluminum oxide particles, and randomly divided into 12 groups (n = 10), according to the cement thickness (50, 100, 150, and 200 μm) and SAC (RelyX U200, PANAVIA SA LUTING Multi, and Maxcem Elite Chroma). The specimens were cemented to the resin composite blocks with SAC, stored in water at 37°C for 24 hours, and subjected to the SBS test. Mode of failure was evaluated under a stereo microscope. The data were statistically analyzed using two-way ANOVA and the Tukey HSD test to compare the differences in mean SBSs between groups at 95% confidence level.Statistical analysis revealed significant differences in SBS (p < 0.05) across the SACs, with the highest mean observed in the 50 μm cement thickness group and decreased as cement thickness increased. PANAVIA SA LUTING Multi exhibited the highest SBS, followed by the RelyX U200 groups, with the lowest SBS observed in Maxcem Elite Chroma groups (p < 0.05). In addition, the predominant mode of failure in all groups, except RelyX U200 and Maxcem Elite Chroma groups with the thickness of 200 μm, was score 4 (no resin cement remained on the zirconia surface).The difference in cement thickness and the type of SAC affected the SBS to zirconia. The lesser the cement thickness, the higher the SBS. 10-MDP-based cements, which provide the highest bond strength to zirconia and low cement thickness, are suggested for zirconia cementation to achieve a strong bond between zirconia and resin cement.
Keywords: zirconia; self-adhesive resin cement; cement thickness